Patient Education About Drug Side Effects on Compliance in Taking Antihypertension Medication: A Rapid Review - Anjani, Aiko Nurrahma; Bekti Sayekti , Muna; Sekar Wijayanti , Nia; Arifah Chofsoh, Salma; Permata Fitrianisa, Salsayabila; Azmiardi, Akhmad (Universitas Mulawarman, 2025)
Treatment compliance is a determinant of the success of therapy, especially in the treatment of hypertension. Education is one way that can be done to influence and increase knowledge of the importance of adherence to treatment to achieve successful antihypertensive drug therapy. Objective: to review articles regarding the influence of education about drug side effects and adherence to taking antihypertensive drugs. Method : review . Results: The results of the educational search study influenced knowledge and compliance in taking hypertension medication. There was a significant difference before and after education was provided regarding adherence to taking antihypertensive medication.